2012
DOI: 10.1111/j.1465-3362.2012.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and its predictors among Asian problem drinkers

Abstract: Significant reductions in drinking frequency and severity are possible for Asian problem drinkers after 12 weeks of outpatient treatment. The identified predictors suggest that more frequent drinkers and patients with past/current psychiatric comorbidities may require a more intensive treatment approach to optimise treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Instead outcome measures such as days with heavy drinking, defined as consumption of certain levels of alcohol in a 30-day period, have been used to define relapse (Soyka and Schmidt, 2009;Manning et al, 2013;Mellentin et al, 2018), yet the definition of controlled drinking as a successful treatment goal may vary between patients and misestimations of alcohol quantities among study participants have been shown to result in overestimations of treatment efficiency and underestimation of relapse (Kirouac et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Instead outcome measures such as days with heavy drinking, defined as consumption of certain levels of alcohol in a 30-day period, have been used to define relapse (Soyka and Schmidt, 2009;Manning et al, 2013;Mellentin et al, 2018), yet the definition of controlled drinking as a successful treatment goal may vary between patients and misestimations of alcohol quantities among study participants have been shown to result in overestimations of treatment efficiency and underestimation of relapse (Kirouac et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As our dataset is small, it may not be representative; however, the ethnic profile of the subjects recruited (Table 1) reflects previous reports. Past studies suggest that the majority of the AUD cases had either Chinese or Indian background [49], while Malay, followed by subjects of Chinese ethnicity, made up the bulk of OUD cases. Future studies should focus on ethnic differences in genetic variations in specific substance types.…”
Section: Discussionmentioning
confidence: 99%
“…According to second theme, the main components recommended for substance abuse rehabilitation according to the research result are as follows: addict’s acceptance of the treatment and taking responsibility of the treatment regarding substance addiction, attendance of family especially father during rehabilitation process, together with health-care support, the implementation of family-based psychological support, commitment to continuous and sustainable fight against addiction, strengthening problem-solving and cognitive skills of the addict, forming a new social life, return to work or school life, reshaping family relationships, reconstruction of family bonds, and feeling of belonging. Manning et al (2013) state that fight against alcohol and substance addiction is a lifelong process, and it is necessary to give psychological support to family members since family is the most important source of support for addicts during this process. Related literature shows that medical treatment given in health facilities is not alone sufficient to provide a long-term solution, and psychological and social support should be given to addicts with the inclusion of parents into the rehabilitation process (Kim, Kwok, Mayes, Potenza, Rutherford, & Strathearn, 2017).…”
Section: Discussionmentioning
confidence: 99%